Improvement of Quality of Life in Dialysis and Diabetic Patients by Skin Dryness and Pruritus Management with an Ecobiological Dermo-Cosmetic Product - Polena H; Chavagnac-Bonneville M; Sayag M (Clinical, Cosmetic and Investigational Dermatology, 2022)
Helena Polena,1 Marlène Chavagnac-Bonneville,1,2 Michèle Sayag1 1NAOS Group, Research and Development Department, Aix-en-Provence, France; 2NAOS Institute of Life Science, Aix-en-Provence, FranceCorrespondence: Helena Polena, NAOS Group, 355 rue Pierre Simon Laplace, Cedex 03, Aix-en-Provence, 13593, France, Tel +33 4 72 11 37 19, Fax +33 4 78 53 82 54, Email helena.polena@naos.comPurpose: Xerosis and pruritus are common chronic dermatological disorders among dialysis and diabetic patients that are frequently underdiagnosed or neglected, which can impact the quality of life of these patients. This study aimed to evaluate the efficacy and safety of a specific dermo-cosmetic product in the treatment of dry skin and pruritus associated with dialysis and diabetes.Patients and Methods: Twenty-nine dialysis patients (mean age 62 years) and 40 diabetic patients (mean age 57 years, 88% type 2) were included in two different single-center open-label uncontrolled clinical trials. All patients presented skin dryness according to the Scaling Roughness Redness and Cracks (SRRC) scale, and pruritus and/or insomnia. They applied the dermo-cosmetic product Medi-Secure Atoderm Xereane (NAOS, Laboratoire Bioderma) once or twice a day. The clinical efficacy (SRRC, pruritus, and insomnia), the skin-related quality of life (Dermatological Life Quality Index, DLQI), and the subjective efficacy were assessed at the inclusion visit and after 28 days of product application, as well as the safety.Results: After 28 days of application, the product significantly reduced the SRRC global score of 83% (0.9± 0.8 vs 5.1± 1.2) and 66% (1.4± 1.2 vs 4.2± 0.5), pruritus intensity of 76% (1.1± 1.3 vs 4.6± 2.1) and 78% (0.9± 1.7 vs 4.2± 2.6), and insomnia intensity of 61% (0.9± 1.3 vs 2.4± 2.3) and 82% (0.9± 1.7 vs 4.8± 2.7) in dialysis and diabetic patients, respectively. Furthermore, the product’s application led to an improvement of the skin-related quality of life of 50% (5.4 vs 2.7; p< 0.0001) in dialysis patients and 71% (6.6 vs 1.9; p< 0.0001) in diabetic patients at D28. In addition, the product was greatly appreciated by all patients for its soothing, comforting, repairing, nourishing, and hydrating effects and was very well tolerated by the entire panels.Conclusion: This specific dermo-cosmetic product significantly reduces skin dryness, pruritus, and insomnia in dialysis and diabetic patients, thereby greatly improves their skin-related quality of life. By managing and avoiding bothersome symptoms associated with their disease or treatment, this ecobiological dermo-cosmetic can prevent serious complications that constitute a substantial burden on their daily life.Keywords: xerosis, itch, uremic, diabetes mellitus, insomnia, emollient